(untitled) (Journal of Advanced Research in Social Sciences, 2025)
This article examines the shift from Islamophobia to neo-Islamophobia in the portrayal of Muslims in post-9/11 cinema. The research explores the evolution of themes such as fear, antagonism, and prejudice via analysing diverse cinematic representations, especially those related to emerging discourses on feminism, LGBTQ rights, and Western cultural standards. The study emphasizes the internalization and externalization of Islamophobia in Western and Arab cultures, highlighting its significant effects on identity, self-esteem, and international relations. This study is a deep dive into the transition in the depiction of Muslims in post-9/11 films from Islamophobia to neo-Islamophobia, offering a comprehensive understanding of the societal implications of this shift.